A novel fucoidan complex-based functional beverage attenuates oral cancer through inducing apoptosis, G2/M cell cycle arrest and retarding cell migration/invasion. (October 2021) - Chen, Pei-Hui; Chiang, Pao-Chang; Lo, Wen-Cheng; Su, Chun-Wei; Wu, Chia-Yu; Chan, Chun-Hao; Wu, Yi-Chieh; Cheng, Hsin-Chung; Deng, Win-Ping; Lin, Hsi-Kuei; Peng, Bou-Yue
Highlights: We have developed a novel fucoidan complex-based functional beverage, designated as VMW-FC. VMW-FC strongly induced apoptosis and G2/M cell cycle arrest in oral cancer cells. VMW-FC inhibited metastatic potential and EMT markers in oral cancer cells. VMW-FC significantly attenuated tumor growth in vivo without further side effects. VMW-FC may be a promising alternative treatment for oral cancer. Abstract: In current study, we have investigated the anti-oral cancer effects of developed functional beverage, which integrates fucoidan complex (FC) with natural/organic ingredients including vegetable juice (V), mulberry (M) and wheatgrass (W), designated as VMW-FC cocktail. FC has been recognized as functional food with nutraceutical characteristics, other cocktail components are known to individually contain luxuriant bioactive factors including sulfated polysaccharides and polyphenols etc., exerting various curative impacts. Our results demonstrated that VMW-FC significantly inhibited oral cancer proliferation in a dose- and time-dependent manner. It also retarded cell cycle regulators (CDKs and cyclins) and upregulated cyclin-dependent kinase inhibitor p21. Additionally, VMW-FC suppressed cell migration along with inhibited EMT markers. Further, VMW-FC significantly attenuated xenograft tumor growth in NOD-SCID mice without further adverse effects. Conclusively, VMW-FC strongly inhibits oral cancer through inducing apoptosis, G2/M cell cycle arrest and reducing migration-related EMT markers, which may be primarily attributed to sulfated polysaccharides in beverage cocktail.